(untitled) (Journal of Medicine, 2026)
Extrapulmonary tuberculosis (EPTB) represents a major but under-recognized element of the tuberculosis (TB) burden in Bangladesh. Although pulmonary TB (PTB) remains the dominant form of the disease, EPTB accounts for a notable proportion of national TB cases, ranging from 15–30% based on hospital and community-level studies. EPTB manifests in variegated anatomical sites—including lymph nodes, pleura, abdomen, bones, urogenital tract, and the central nervous system—often presenting with nonspecific symptoms that overlap with malignancy, autoimmune disorders, or bacterial infections.These diagnostic challenges combined with the paucibacillary nature of EPTB, complicate clinical evaluation and contribute to delays in management. Recent improvements in molecular diagnostics such as Gene Xpert MTB/RIF have enhanced case detection; however, access remains uneven across Bangladesh, especially in rural and district-level facilities. This review synthesizes the current evidence on extrapulmonary tuberculosis (EPTB) in Bangladesh, covering epidemiology, risk factors, pathogenesis, clinical presentation, diagnosis, treatment, and systemic challenges. It highlights local research published in BanglaJOL, National TB Program (NTP) data, tertiary hospital studies, and WHO guidance adapted to the Bangladeshi context.Although less common than pulmonary MDR-TB, drug-resistant EPTB presents significant clinical and public health challenges. Reducing EPTBrelated morbidity and long-term complications requires multisectoral strategies, which includes enhanced laboratory capacity, standardized diagnostic protocols, decentralized molecular testing, and targeted clinician training. This review seeks to assist clinicians, researchers, and policymakers by consolidating current knowledge and identifying key gaps and priorities for future action. J MEDICINE 2026; 27(1): 40-48